2020
DOI: 10.1002/lom3.10378
|View full text |Cite
|
Sign up to set email alerts
|

Using machine learning to correct for nonphotochemical quenching in high‐frequency, in vivo fluorometer data

Abstract: In vivo fluorometers use chlorophyll a fluorescence (Fchl) as a proxy to monitor phytoplankton biomass. However, the fluorescence yield of Fchl is affected by photoprotection processes triggered by increased irradiance (nonphotochemical quenching; NPQ), creating diurnal reductions in Fchl that may be mistaken for phytoplankton biomass reductions. Published correction methods are mostly designed for pelagic oceans and are ill suited for inland waters or for high‐frequency data collection. A machine learning‐bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 83 publications
(140 reference statements)
1
6
0
Order By: Relevance
“…Unfortunately, the coupling of elevated nighttime F chl (due to FIZ) with depressed daytime F chl (due to NPQ) may lead to exaggerated differences between day and nighttime values. In this study, F chl data from the exclusion experiment revealed fluorescence quenching in both open and exclusion treatments and its magnitude was congruent with other studies in Lake George (Lucius et al 2020). However, only the open water treatment showed the characteristic, large‐magnitude spikes associated with FIZ bias, indicating that these nighttime F chl increase where not associated with fluorescence quenching.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Unfortunately, the coupling of elevated nighttime F chl (due to FIZ) with depressed daytime F chl (due to NPQ) may lead to exaggerated differences between day and nighttime values. In this study, F chl data from the exclusion experiment revealed fluorescence quenching in both open and exclusion treatments and its magnitude was congruent with other studies in Lake George (Lucius et al 2020). However, only the open water treatment showed the characteristic, large‐magnitude spikes associated with FIZ bias, indicating that these nighttime F chl increase where not associated with fluorescence quenching.…”
Section: Discussionsupporting
confidence: 93%
“…As F chl is a common proxy for phytoplankton biomass, NPQ correction methods have been developed to generate F chl data more representative of true phytoplankton biomass. Methods for correction often use nighttime data as a reference for comparison and correction of temporally adjacent daytime data in marine (Thomalla et al 2018; Xing et al 2018) and freshwater environments (Lucius et al 2020). However, nighttime data that are collected at high frequencies (e.g., once per minute) may be subjected to FIZ, leading to the use of biased coefficients when correcting for daytime NPQ.…”
Section: Discussionmentioning
confidence: 99%
“…Optimization of fluorescence sensors through machine learning can assist in this field of research, including detection of anomalies to trigger management responses (Almuhtaram et al, 2021) and correction of light-induced fluorescence quenching (Lucius et al, 2020;Rousso et al, 2021). The application of machine learning techniques to predict cyanobacteria species dominance based on environmental conditions has been suggested as a way to improve calibration of fluorescence sensors and to provide species-specific information in real time to support improved cyano-HAB management (Rousso et al, 2020).…”
Section: Implications For Water Monitoring and Cyanohab Managementmentioning
confidence: 99%
“…daily, weekly, and interannually) in a cost-effective way (2,3). Reliability of hourly measurements, however, remains problematic (4)(5)(6)(7). Although Chla concentration is estimated by this method, it is in vivo fluorescence (IVF) that is actually measured.…”
Section: Introductionmentioning
confidence: 99%
“…IVF is the light reemitted by photosystems from excited to ground states. Chla-specific IVF (IVF B ) is variable and can be affected by phytoplankton taxonomy (8,9), cell size (10), nonphotochemical quenching (4,7,11,12,13), temperature (1,14) and nutrient status (15). Nonphotochemical quenching (NPQ) is a protection mechanism used by plants and algae to dissipate excess absorbed light energy as heat (i.e.…”
Section: Introductionmentioning
confidence: 99%